Development of a measuring system on ski deflection and contacting snow pressure in turns - Kagawa, H.; Yoneyama, T.; Tatsuno, D.; Scott, N.; Osada, K. (Science and Skiing IV, 2009)
INTRODUCTION: Deflection of the ski and the ski-snow contacting pressure are both important factors in the ski turn. But they have not been directly measured precisely in the actual turn on the snow slope. In this study, a new measuring System to detect both the ski deflection and the ski-snow contacting pressure is developed.